2014
DOI: 10.1007/s11172-014-0758-5
|View full text |Cite
|
Sign up to set email alerts
|

Activation of M—H bond upon the complexation of transition metal hydrides with acids and bases

Abstract: Features of the electronic structure of adducts of transition metal hydride complexes (Cp*M(dppe)H, dppe is the 1,2 (diphenylphosphino)ethane, M = Fe, Ru, Os; CpM(CO) 3 H, M = Mo, W) with acids and bases were analyzed with the ADF2014 program using energy decomposition analysis (EDA) by the Ziegler-Rauk method combined with the natural orbitals for chemical valence theory (ETS NOCV). The nature of orbital interactions in the complex determines the reaction pathway:  MH  * OH interaction leads to the proton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…DFT calculations , have shown that the MH bond polarization in CpMH­(CO) 3 is similar to that in HCF 3 . As expected, the decrease in the MH bond polarization [Δpol­(MH), Table ] caused by hydrogen bonding reflects an increase in positive charge on the metal-bound hydrogen (by 0.053–0.084 units), as expected for a proton donor.…”
Section: Mh···y Hydrogen Bonds and Proton Transfer From Transition-m...mentioning
confidence: 95%
See 3 more Smart Citations
“…DFT calculations , have shown that the MH bond polarization in CpMH­(CO) 3 is similar to that in HCF 3 . As expected, the decrease in the MH bond polarization [Δpol­(MH), Table ] caused by hydrogen bonding reflects an increase in positive charge on the metal-bound hydrogen (by 0.053–0.084 units), as expected for a proton donor.…”
Section: Mh···y Hydrogen Bonds and Proton Transfer From Transition-m...mentioning
confidence: 95%
“…Similarly, in XH···HM bonds, the transfer of electron density takes place from the interacting site of the base σ MH orbital to the σ* XH orbital of an acid. In complex transition-metal hydrides, the σ MH orbitals need not correspond to the HOMO (contrary to the majority of simple main-group hydrides) but specifically these orbitals are involved in charge transfer to σ* XH . …”
Section: Spectral Criteria Structural Parameters and Energetics Of Di...mentioning
confidence: 99%
See 2 more Smart Citations
“…The easy polarization of M−H bond and relatively low electron density on the hydride ligand in free CpMH(CO) 3 complexes allow the interaction not only with bases but also with Lewis acids. The calculations on their adducts with BH 3 as a mild Lewis acid revealed the σ M−H to LP* B donation (Figure ) leading to the increase of the electron density on the metal bound hydrogen (Table ) . In a sense, the [M]H⋅⋅⋅BH 3 interaction is similar to the dihydrogen bonding.…”
Section: Orbital Interactions and Z−h Bond Polarization In Hydrogen Bmentioning
confidence: 90%